2019
DOI: 10.1186/s12889-019-7550-2
|View full text |Cite
|
Sign up to set email alerts
|

Effective implementation of primary school-based healthy lifestyle programmes: a qualitative study of views of school staff

Abstract: Background Primary schools are valuable settings to implement healthy lifestyle (healthy eating and physical activity) interventions, aimed at targeting childhood obesity. This study explored school staff perceptions of factors that hinder and enable successful implementation and sustainability of healthy lifestyle interventions in primary schools. Qualitative data was pooled and analysed from two evaluations carried out in primary schools in North England: a feasibility study of a nutrition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 30 publications
5
84
0
6
Order By: Relevance
“…Moreover, differences in characteristics related to the working group members, i.e., interpretation of the approach, the degree of practice-oriented thinking, the presence of one or more champions, and the dynamics within the working group, but also the differing degrees of influence of factors within the outer setting (i.e., support from the school board, national health-promoting trends, and the presence of and the capacity to collaborate with potential partners) resulted in different implementation processes. Other studies also found these contextual factors to facilitate and hinder implementation of school health-promoting interventions [33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, differences in characteristics related to the working group members, i.e., interpretation of the approach, the degree of practice-oriented thinking, the presence of one or more champions, and the dynamics within the working group, but also the differing degrees of influence of factors within the outer setting (i.e., support from the school board, national health-promoting trends, and the presence of and the capacity to collaborate with potential partners) resulted in different implementation processes. Other studies also found these contextual factors to facilitate and hinder implementation of school health-promoting interventions [33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Schools experienced children's nutrition behavior as being more difficult to change at school than physical activity [34]. This is because collaboration between school and parents is important in creating a healthy nutrition-promoting environment, but this collaboration is difficult to achieve [58]. Parents have a big influence on children's nutrition consumption, also at school, because Dutch children bring home-packed lunches and drinks to school [12].…”
Section: Discussionmentioning
confidence: 99%
“…According to results of the researches conducted in Northern England, it has been noted that educational institutions should utilize strategies as to long-term engagement of school employees, schoolchildren and their parents. In order to provide sustainability, it has been noted that the programs should be integrated in long-term curricula and school policy, with steady support of principals and staff [15].…”
Section: Discussionmentioning
confidence: 99%